2015
DOI: 10.1002/ccd.26240
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of a dedicated stent in coronary bifurcations with large side branches: A subanalysis of the randomized TRYTON bifurcation study

Abstract: Analysis of the TRYTON Trial cohort of SB ≥2.25 mm supports the safety and efficacy of the Tryton SB stent compared with a provisional stenting strategy in the treatment of bifurcation lesions involving large SBs. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…The SB mean RVD was 1.58 ± 0.41 as assessed by QCA (Table ). A subanalysis of the Tryton randomized trial by Généreux et al showed that 59% of enrolled patients had a QCA‐assessed SB RVD ≤ 2.25 mm (Core Lab QCA) . These findings show expected differences between visual estimates of vessel size and QCA and highlight the need for baseline QCA to enhance adequate patient selection.…”
Section: Discussionmentioning
confidence: 99%
“…The SB mean RVD was 1.58 ± 0.41 as assessed by QCA (Table ). A subanalysis of the Tryton randomized trial by Généreux et al showed that 59% of enrolled patients had a QCA‐assessed SB RVD ≤ 2.25 mm (Core Lab QCA) . These findings show expected differences between visual estimates of vessel size and QCA and highlight the need for baseline QCA to enhance adequate patient selection.…”
Section: Discussionmentioning
confidence: 99%
“…The failure to meet the primary endpoint was due mainly to an increased incidence of periprocedural myocardial infarction (PPMI) in the Tryton stent group. A post hoc analysis of the intended population restricted to lesions involving SBs with a reference vessel diameter $2.25 mm demonstrated superior angiographic results and a numeric reduction in target vessel failure within the noninferiority margin; however, because of the nature (retrospective, non-prespecified) of this subanalysis, an additional prospective study was required to validate these findings (13).…”
mentioning
confidence: 80%
“…The Tryton Pivotal RCT was also the largest RCT to exclusively studied bifurcation lesions(12). The pivotal randomized trial(12) and its large SB post hoc analysis(13), in conjunction with the present study, not only demonstrate the safety and efficacy of the Tryton Side Branch…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…In this edition of the journal, Genereaux et al present results from the TRYTON study which evaluated routine side branch (SB) stenting with a novel bare metal stent (BMS) designed for true bifurcation lesions (Medina 1,1,1; 1,0,1; 0,1,1) and compared it to a strategy of balloon angioplasty with provisional stenting.…”
mentioning
confidence: 99%